Notes on the Ottoman-Habsburg Antagonism in South East Europe and Its Climax During the 17th Century - Marcinkowski, Muhammad Ismail (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Notes on the Ottoman-Habsburg Antagonism in South East Europe and Its Climax During the 17th Century